Teknologi Internet of Things (IoT) pada Tanaman Selada dan Pakcoy Hidroponik dengan Menggunakan Perhitungan MAPE - Ramsari, Nopi; Hidayat, Teddy (Journal of Applied Informatics and Computing, 2023)
Hydroponics is a technique of cultivating plants without using soil, instead using water as a growing medium. One of the advantages of hydroponics is that it has a high selling value and does not require a large area. To make good quality plants, you must pay attention to factors such as: nutritional needs, pH, temperature and light intensity around the hydroponic environment. By using the Internet of Things (IoT), we can monitor and control these factors, so hydroponic plants can grow well. In this study we used two samples of different types of plants, such as pak choy and lettuce. Microcontroller as the main controller of all IoT components. The sensors used are TDS sensors, PH sensors, temperature sensors and light sensors. The softwares tools that we used are the Arduino IDE and the CodeIgniter Framework to develop the user interface display so that it is easy to use by users using web browsers or smartphone devices. Testing the concentration of nutrients with the TDS sensor uses MAPE to get a yield of 13,17 % for salad plants and 7,32 % for pak choy plants while for testing the pH of the water the results were 13,95% for salad plants and 13,91% for pak choy plants. Because the MAPE value is 10 "“ 20%, it shows the ability of the IoT for monitoring and controlling nutrient concentration and pH content in hydroponic systems is good. With IoT technology, we can monitor and control plants in real-time automatically so that hydroponic plants continue to grow properly with minimal human intervention.